Internal jugular phlebectasia in an African adult - Ogbole, Godwin I (BMJ Publishing Group, 2010)
Jugular vein phlebectasia is a rare venous anomaly commonly presenting as a unilateral neck swelling in children and adults. Its aetiology is unknown and its detection may have increased with availability of better imaging facilities. Due to its rarity, a high index of suspicion is required once other causes of neck swelling are excluded. The few reported cases are mainly in children and non-Africans adults. The authors report the case of a 54-year-old Nigerian woman presenting for the first time with a progressive, intermittent, painless right neck swelling, which was demonstrated on Doppler ultrasound and CT angiography to be an internal jugular phlebectasia. She had satisfactory surgical excision of the dilated segment for cosmetic reasons.